Piloting Benefit-Sharing Mechanisms and Influencing National Policy in Peru - CGIAR Challenge Program on Water and Food (2014)
Water Use in the Cañete River Basin People who live in a healthy watershed benefit from its steady supply of water in many different ways, using it for households, agriculture, and industry. In many cases, however, the benefits derived from water are inequitably distributed among water users. Mechanisms that redistribute the benefits are known as benefit- sharing mechanisms and are most likely to be successful in places where water supply from ecosystems upstream is combined with a high demand for water downstream. This is the case in the Cañete River basin in Peru, where farmers, rural households, hydropower companies, industry, and the population of Cañete town rely on the ecosystem upstream to supply them with water.